Crescimento de espécies arbóreas e respostas produtivas e fisiológicas da cana-de-açúcar em sistemas agroflorestais - Elli, Elvis Felipe (2016)
The aim of the study was to evaluate the growth of tree species and productive and physiological responses of sugarcane in agroforestry systems. The research was conducted from 2007 to 2014, in the city of Frederico Westphalen, Rio Grande do Sul, Brazil, with geographic location 27 ° 22'S, 53 ° 25'W and 480 m altitude. The experimental design was a randomized complete block with three replications. The following tree species were used: Eucalyptus urophylla S.T. Blake x Eucalyptus grandis Hill ex Maiden, Mimosa scabrella Benth., Parapiptadenia rigida, Peltophorum dubium (Spr.) Taubert e Schizolobium parahybae (Vell.) Blake. The species were divided into two agroforestry systems arrangements, strip and line systems. In strip system, forest species were divided separate strips by 12m, each composed of three lines, in which the plants were spaced 3x3m. The sugarcane (Saccharum officinarum L.) was distributed in eight lines (between the tracks, within 12m) and two lines in range (between the rows of trees). In line system, forest species were distributed in spacing 6x1,5m; i.e., 6m between line and 1.5 m between plants in the line, and the sugarcane distributed in three lines (between the lines of trees). In both systems, the cultivate sugarcane was the IAC 87-3396, which was distributed in spacing 1.20m. Both lines of sugarcane as the trees were oriented east-west direction. The tree variables analyzed were: collar diameter (cm), diameter at breast height (cm), plant height (m) and mean crown diameter (m). The variables analyzed in sugarcane were: stem mass (t ha-1), stem length (m), stem diameter (mm), number of nodes, juice volume (m3 ha-1), degree Brix, amount of sucrose (t ha-1), photosynthetically active solar radiation (μmol s-1 m-2), leaf temperature (° C), resistance to vapor diffusion (s cm-1) and transpiration (s-1 H2O mmol m-2) of leaves. The meteorological variables occurring during the study were obtained through Climatological the National Institute of Meteorology Station, located at 1500 m from the study site, with geographic location 27°39'S and 53°43'W. The growth of tree species was influenced by plant arrangement in agroforestry systems. In addition, meteorological elements changed the growth of forest species and should be taken into account to carry out a proper planning and appropriate choice of tree species that make up the system. Among the species studied, eucalypt showed higher growth in stem diameter, diameter at breast height, mean crown diameter and total height. The strip system provided increased growth of most tree species (eucalyptus, canafístula and bracatinga). This system allowed greater incidence of photosynthetically active radiation under the trees, resulting in increased productivity, increased resistance to vapor diffusion and reduced transpiration from leaves of sugarcane.